Assessing Foot Loads in Continuous Passive Motion (CPM) and Active Knee Joint Motion Devices - Stolz, Benedikt; Grim, Casper; Lutter, Christoph; Gelse, Kolja; Schell, Monika; Swoboda, Bernd; Carl, Hans-Dieter; Hotfiel, Thilo (Sportverletzung-Sportschaden, 2019)
BACKGROUND: Continuous passive motion (CPM) and active knee joint motion devices are commonly applied after various surgical procedures. Despite the growing use of active motion devices, there is a paucity of data comparing plantar loads between the different mobilization techniques. The aim of this study was to investigate foot loads during knee joint mobilization in continuous passive and active knee joint motion devices and to compare this data to the physiological load of full weight-bearing. PATIENTS/MATERIAL AND METHODS: Fifteen healthy participants (7 women and 8 men, 25 ± 3 years, 66 ± 6 kg, 175 ± 10 cm, BMI 21.9 ± 2) were recruited. Plantar loads were measured via dynamic pedobarography using a continuous passive motion device (ARTROMOT-K1, ORMED GmbH, Freiburg, Germany) and an active motion device (CAMOped, OPED AG, Cham, Switzerland), each with a restricted range of motion of 0-0-90° (ex/flex) and free ROM for the knee joint. For the active motion device, cycles were performed at four different resistance levels (0-III). Data were assessed using the pedar® X system (Novel Inc., Munich, Germany), which monitors loads from the foot-sole interface. Force values were compared between motion devices and normal gait, which served as the reference for conditions of full weight-bearing. P-values of < 0.05 were considered statistically signiﬁcant. RESULTS: Normal gait revealed peak forces of 694 ± 96 N, defined as 100 %. The CPM device produced plantar forces of less than 1.5 N. Using the active motion device in the setting of 0-0-90° produced foot loads of < 1.5 N (resistance 0-II) and 3.4 ± 9.3 N with a resistance of III (p < 0.001). Conditions of free ROM resulted in foot loads of 4.5 ± 4.5 N (resistance 0), 7.7 ± 10.7 N (resistance I), 6.7 ± 10.4 (resistance II) and 6.7 ± 6.9 N with a resistance of III (p < 0.001), corresponding to 0.6 %, 1.1 %, 1.0 % and 1.0 % of full weight-bearing, respectively. CONCLUSION: Motion exercises of the knee joint can be performed both with passive and active devices in accordance with strict weight-bearing restrictions, which are often recommended by surgeons. Also, active motion devices can be used when the ankle joint or foot have to be offloaded. Further studies assessing intraarticular joint load conditions have to be performed to confirm the findings obtained in this study.
EVALuna2:205192